Tiotropium/Olodaterol treatment reduces cigarette smoke extract-induced cell death in BEAS-2B bronchial epithelial cells - Cheng-hsiung Chen; Yi-Rong Li; Sheng-Hao Lin; Hsiu-Hui Chang; Woei-Horng Chai; Po-Chiang Chan; Ching-Hsiung Lin (BMC, 2020)
Abstract Background Cigarette smoking is a critical risk factor for the destruction of lung parenchyma or the development of emphysema, which is characteristic of COPD. Disruption of epithelial layer integrity may contribute to lung injury following cigarette smoke extract (CSE) exposure. Tiotropium/olodaterol acts as a bronchodilator for COPD treatment; however, the effect of dual bronchodilators on epithelial cell injury and its underlying mechanism remain unclear. In this study, we evaluated the effect of tiotropium/olodaterol on CSE-mediated cell death and the underlying mechanisms. Methods Cell viability was determined using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Apoptosis, necrosis, and autophagy were evaluated using flow cytometry. Autophagy-related protein, phosphorylated ERK, expression was determined using Western blotting. Results Tiotropium/olodaterol significantly inhibited CSE-induced cell death, mitochondria dysfunction, and autophagy, which had no significant effect on apoptosis or necrosis in BEAS-2B human bronchial epithelial cells. Moreover, tiotropium/olodaterol attenuated CSE-induced upregulation of JNK. Conclusions CSE induced cell death and caused consistent patterns of autophagy and JNK activation in BEAS-2B human bronchial epithelial cells. Tiotropium/olodaterol treatment protected bronchial epithelial cells from CSE-induced injury and inhibited activation of autophagy and upregulation of JNK phosphorylation. These results indicate that tiotropium/olodaterol may protect epithelial cells from the deleterious effects of CSE exposure, which is associated with the regulation of autophagy and JNK activation.